Dampak Pembelajaran Berbasis Game terhadap Motivasi Belajar Siswa Kelas V UPTD SDN Pendabah 3 - Siti Maimunah; Kusmiyati Kusmiyati (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
The purpose of this study is to explore how game-based learning impacts the learning motivation of Grade V students at UPTD SDN Pendabah 3. A literature review method was employed to analyze relevant academic sources. The results indicate that game-based learning, through challenges and rewards, can enhance students' intrinsic motivation. This study concludes that game-based learning has significant potential as an innovative teaching strategy, despite certain challenges in its implementation, such as costs and teacher training.